BASYARNAS as a Place for Dispute Resolution of Musyarakah Financing in Sharia Banking in the Disruption Era - Evi Eka Elvia; Abdul Mujib; Azhar Nor; Muhammad Imanuddin Akbar (El-Mashlahah, 2023)
The practice of musyarakah financing in Islamic banking allows conflicts to occur between parties, the most dominating conflict in financing practices is the default. Arbitration is one of the non-litigation dispute resolution forums that can be used in resolving musyarakah financing disputes in Islamic banking. The purpose of this study was to analyze the settlement of default disputes on musyarakah financing practices which were resolved through the Badan Arbitrase Syariah Nasional (BASYARNAS). This research is normative legal research using a statutory approach. The results of the study show that financing disputes in Islamic banking occur because there are default factors behind them, namely intentional factors and negligence factors. Both of these factors can give a loss to the creditor (Bank) as the provider of funds. Musyarakah financing dispute settlement in Islamic banking is an agreement of the disputing parties. If it is contained in the agreement clause which states that dispute resolution is carried out through BASYARNAS, then BASYARNAS has the authority to resolve the dispute as stipulated in the law. In an era of disruption full of change and innovation, arbitration with the online system is an important matter in resolving disputes at BASYARNAS.